Doped perovskite type catalyst for enhancing PMS activation as well as preparation method and application of doped perovskite type catalyst
By doping Mo atoms in the perovskite structure, the LaCo0.95Mo0.05O3-δ catalyst was prepared, which solved the problem of degradation of organic pollutants in water, achieved improvement of the stability and activation performance of the catalyst, and had rapid degradation and reusability. Advantages of
Patent Information
- Application Number
- CN202411539652.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to effectively degrade organic pollutants such as paracetamol in water, especially the challenge of improving catalyst stability and activation performance while avoiding active metal leaching and secondary pollution.
By doping Mo atoms into the perovskite structure, LaCo0.95Mo0.05O3-δ catalyst was prepared, and prepared by sol-gel method, combined with PMS activation, and efficiently degraded organic pollutants in water.
It significantly improves the stability of the catalyst and PMS activation performance, rapidly degrades paracetamol in water, has good reusability and a low-cost preparation method.
Smart Images

Figure CN119259068A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wastewater treatment catalyst material development, and relates to a doped perovskite catalyst for enhancing PMS activation, and a preparation method and application thereof. Background Art
[0002] Paracetamol, as one of the most effective analgesics and antipyretics, has been widely used and is present in wastewater treatment effluents and surface waters at levels of μg / L. Therefore, there is an urgent need to develop effective remediation technologies to avoid the accumulation of the drug in aquatic environments. Advanced oxidation processes (AOPs) have been investigated as promising alternatives for the degradation of organic pollutants in aquatic environments. In the past decade, peroxymonosulfate (PMS)-based AOPs have attracted extensive attention by generating reactive oxygen species (ROS) via heat, UV irradiation, transition metal catalysis, and are highly efficient over a wide pH range.
[0003] Among various activation techniques, transition metal-based heterogeneous catalysts have great potential due to their wide range of operating conditions, no need for additional energy, and high efficiency, mainly due to the generation of in situ oxidative radicals. As well as non-radical oxidation pathways (electron transfer, Fe / Co-oxo complexes, etc.). In heterogeneous catalytic PMS activation, co-catalysts are highly efficient and can further promote the catalytic ability of. However, due to the inherent toxicity of Co, appropriate heterogeneous catalysts should be stabilized in a stable crystal structure to reduce Co leaching and avoid secondary contamination.
[0004] Perovskite oxides with the chemical formula ABO3 have emerged as promising candidates for multiphase PMS activation. The A-site cation is usually larger than the B-site cation, which is surrounded by six oxygen anions in a hexahedral coordination. 6+ The octahedral coordination has a highly stable oxidation state with similar ionic radius and thus could be an ideal candidate for Co substitution.
[0005] The activation ability of PMS is enhanced by doping Mo atoms at the B site of the perovskite structure. By adjusting the Mo content, a phase transition from rhombohedral to cubic-like structure is achieved, in which LaCo 0.95 Mo 0.05 O 3-δ The compounds are located at the so-called morphological phase boundary (MPB), which significantly improves the activation properties of the PMS and the stability of the catalyst. Summary of the invention
[0006] The object of the present invention is to provide a doped perovskite catalyst for enhancing PMS activation and a preparation method and application thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A doped perovskite catalyst for enhancing PMS activation and a preparation method and application thereof, comprising the following steps: step 1, La(NO3)3·6H2O, Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O, dissolved in deionized water, and added a complexing agent. Step 2. The synthesized mixture was heated at 80°C under continuous magnetic stirring until a gel was formed. Step 3. The obtained gel was further dried in an oven at 110°C for 12 hours, and then the precursor was transferred to a crucible and annealed in a furnace at 700°C for 5 hours at a heating rate of 5°C / min to obtain the catalyst LaCo 0.95 Mo 0.05 O 3-δ .
[0009] Furthermore, in step 1, La(NO3)3·6H2O, Co(NO3)2·6H2O and (NH4)6Mo7O 24 4H2O is 10mmol, deionized water is 20mL, and the complexing agent is 20mmol citric acid.
[0010] The second object of the present invention is to use the prepared catalyst to activate PMS to degrade organic pollutants in water, especially paracetamol.
[0011] The catalyst activates PMS to degrade organic pollutants in water, the steps are as follows:
[0012] As the best solution of the present invention, step 1, the experiment of suspending the catalyst was carried out in a 250mL beaker, 25±0.5℃, and continuous stirring at 300rpm. 0.5mM PMS and 0.2g / L catalyst were added to 100mL of 10mg / L paracetamol solution. The initial pH was adjusted by reducing the concentration of nitric acid and sodium hydroxide to 0.1M. 1mL solution samples were regularly extracted at given time intervals and filtered through a 0.45μm cellulose filter. Step 2, the sample was mixed with 0.5mL MeOH to quench the degradation reaction, and the residual paracetamol concentration was analyzed by high performance liquid chromatography (HPLC). Step 3, in order to test the reusability of the catalyst, the solution after the reaction was filtered with a 0.45μm cellulose filter and then washed to collect the catalyst. The filter was then dried at 80℃ for the next cycle.
[0013] The beneficial effects of the present invention are as follows:
[0014] 1. Efficiently activate PMS to produce high concentrations of sulfate free radicals.
[0015] 2. Enhanced the stability of the catalyst and reduced the leaching of active metals.
[0016] 3. The preparation method is simple, low cost and easy to mass produce.
[0017] 4. The catalyst prepared by the sol-gel method of the present invention can quickly activate PMS and degrade paracetamol in water in a short time, has the advantages of good treatment effect and reusability, and provides a new idea for the degradation of organic matter. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Proposed mechanism for PMS activation by LCMO005
[0019] Figure 2 XRD curves (a) and N2 adsorption-desorption isotherms (b) of LCO in Comparative Example 1, LCMO005 in Comparative Example 2, LCMO010 in Comparative Example 3, and LCMO020 in Comparative Example 4
[0020] Figure 3 TEM micrographs (a, b, c) and HRTEM micrographs (d, e, f) of LCO in Comparative Example 1, LCMO005 in Comparative Example 2, and LCMO010 in Comparative Example 3
[0021] Figure 4 Paracetamol removal diagram (a) and PMS decomposition diagram (b) for LCO in Comparative Example 1, LCMO005 in Comparative Example 2, LCMO010 in Comparative Example 3, and LCMO020 in Comparative Example 4
[0022] Figure 5 The effect of different free radical scavengers on the removal of paracetamol using LCMO005 as the catalyst in Comparative Example 1 (a); the effect of FFA (1mM) and MeOH (100mM) on the decomposition of PMS using LCMO005 as the catalyst (b); the effect of MeOH (100mM) on the removal of paracetamol using different catalysts (c); the ESR spectrum of LCMO005 as the catalyst using 20mM DMPO (upper) and 20mM TEMP (lower) as spin traps (d)
[0023] Figure 6 The time-dependent OCP curves (a) and time-ampere curves (b) of LCO in Comparative Example 1, LCMO005 in Comparative Example 2, LCMO010 in Comparative Example 3, and LCMO020 in Comparative Example 4 are shown in FIG.
[0024] Figure 7 Normalized XANES spectra of the Cok edge (a) and Mok edge (b) of the reference compound (dashed line) and the sample (solid line), where the scaling of the sample absorption edge is shown. Fourier transform model of the k3χ(k) spectra of the Cok edge (c) and Mok edge (d)
[0025] Figure 8 The effects of catalyst dosage (a), PMS dosage (b), different pH values (c) and coexisting anions (2 mM) (d) on the removal of paracetamol using LCMO005 as the catalyst in Comparative Example 1 are shown in Figure 1.
[0026] Fig. 9 (a) XRD patterns of the original and recycled LCMO005 in Comparative Example 1; (b) Effect of experimental period on paracetamol removal; (c) Leaching of Co to LCO in Comparative Example 1, LCMO005 in Comparative Example 2, LCMO010 in Comparative Example 3, and LCMO020 in Comparative Example 4 at different initial pH values
[0027] Fig.10 LCMO005 and catalyst suspension in comparative example 1 for paracetamol removal (a) and reaction intermediate spectrum (b) with deposition (catalyst suspension experiment also includes UVC) DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0029] Comparative Example 1: La(NO3)3·6H2O, Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O (total 10mmol) was weighted and dissolved in 20mL deionized water with 20mmol citric acid as complexing agent. The synthesized mixture was heated at 80℃ with continuous magnetic stirring until gel formation. The obtained gel was further dried in an oven at 110℃ for 12 hours. Then, the precursor was transferred to a crucible and annealed in a furnace at 700℃ for 5 hours with a heating rate of 5℃ / min to synthesize the catalyst LaCo 1-x Mo x O 3-δ , when x=0, it is LaCoO 3-δ , denoted as LCO.
[0030] Comparative Example 2: La(NO3)3·6H2O, Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O (total 10mmol) was weighted and dissolved in 20mL deionized water with 20mmol citric acid as complexing agent. The synthesized mixture was heated at 80℃ with continuous magnetic stirring until gel formation. The obtained gel was further dried in an oven at 110℃ for 12 hours. Then, the precursor was transferred to a crucible and annealed in a furnace at 700℃ for 5 hours with a heating rate of 5℃ / min to synthesize the catalyst LaCo 1-x Mox O 3-δ , when x = 0.05, it is LaCo 0.95 Mo 0.05 O 3-δ , denoted as LCMO0005.
[0031] Comparative Example 3: La(NO3)3·6H2O, Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O (total 10mmol) was weighted and dissolved in 20mL deionized water with 20mmol citric acid as complexing agent. The synthesized mixture was heated at 80℃ with continuous magnetic stirring until gel formation. The obtained gel was further dried in an oven at 110℃ for 12 hours. Then, the precursor was transferred to a crucible and annealed in a furnace at 700℃ for 5 hours with a heating rate of 5℃ / min to synthesize the catalyst LaCo 1-x Mo x O 3-δ , when x = 0.1, it is LaCo 0.9 Mo 0.1 O 3-δ , denoted as LCMO010.
[0032] Comparative Example 4: La(NO3)3·6H2O, Co(NO3)2·6H2O and (NH4)6Mo7O 24 ·4H2O (total 10mmol) was weighted and dissolved in 20mL deionized water with 20mmol citric acid as complexing agent. The synthesized mixture was heated at 80℃ with continuous magnetic stirring until gel formation. The obtained gel was further dried in an oven at 110℃ for 12 hours. Then, the precursor was transferred to a crucible and annealed in a furnace at 700℃ for 5 hours with a heating rate of 5℃ / min to synthesize the catalyst LaCo 1-x Mo x O 3-δ , when x = 0.2, it is LaCo 0.8 Mo 0.2 O 3-δ , expressed as LCMO020.
[0033] Comparative Example 5, the experiment of suspended catalyst was carried out in a 250mL beaker, 25±0.5℃, and continuous stirring at 300rpm. 0.5mM PMS and 0.2g / L catalyst were added to 100mL of 10mg / L paracetamol solution. The initial pH was adjusted by reducing the concentration of nitric acid and sodium hydroxide to 0.1M. 1mL solution samples were regularly extracted at given time intervals and filtered through a 0.45μm cellulose filter. The sample was mixed with 0.5mL MeOH to quench the degradation reaction, and the residual paracetamol concentration was analyzed by high performance liquid chromatography (HPLC). In order to test the reusability of the catalyst, the solution after the reaction was filtered with a 0.45μm cellulose filter and then washed to collect the catalyst. The filter was then dried at 80℃ overnight for the next cycle.
[0034] refer to Figure 2 As shown in Figure 2, when the Mo content increases, both the A and B lattice parameters show a contraction opposite to the increase in the C axis. 6+ The radius of (0.59A) and Co 3+ (0.545A) and much smaller than La 3+ (1.36A), so Mo is more suitable to be located in the octahedral position rather than the rhombohedral position. In the octahedral coordination, Mo 6+ (0.59A) greater than Co 3+ (0.545A) is expected to increase. In addition, Mo 6 + Substitution of Co 3+ Partial reduction to Co 2+ , and its size is also higher (0.65A). In addition, with the increase of Mo dopant content, the characteristic diffraction peak at ~33° (see Figure 2 The magnification in a) gradually shifts to lower angles, indicating that the substitution of Mo for Co increases the unit cell parameters. The undoped LCO compound crystallizes in the R-3c rhombohedral space group, and a structural phase transition from R-3c to cubic Pm-3m space group occurs when the Mo doping level is greater than 5%. There is good agreement between the fittings from LCMO005 to R-3c and cubic Pm-3m, which clearly indicates the presence of an MPB in this composition range. The distance between the Co-O octahedra is shorter throughout the MPB, increasing the crystal strain due to the compression of the octahedra. LCMO010 crystallizes in the cubic Pm-3m space group, and further increasing the Mo content (LCMO020) forms a non-stoichiometric La 1-x Co 1-y Mo y O 3-δ Cubic perovskite and La2MoO6 as secondary phases indicate that the solubility limit is reached at room pressure. N2 adsorption-desorption isotherms of different samples are shown in Figure 2As shown in b. LCO has the lowest BET surface area value of 5.38 m 2 / g, and the surface areas increased significantly to 10.18, 11.15, and 11.13 m2 after doping with 5%, 10%, and 20% Mo, respectively. 2 / g. Figure 3 Representative low-magnification TEM images of LCO, LCMO005, and LCMO010 are depicted in Figures 3a, 3b, and 3c, respectively, showing the aggregation of perovskite nanoparticles with a diameter of around 50 nm.
[0035] refer to Figure 4 As shown in a, the combined effect of PMS and perovskite catalyst significantly improves the removal efficiency of paracetamol, indicating that LCO and its derivative cubic perovskite are effective activations. At the same time, the degradation of pollutants and the removal of paracetamol are related to both the crystal structure and specific surface area of perovskite. LCO perovskite has the lowest symmetry and specific surface area, and the kinetic constant for the degradation of target pollutants is also the lowest. 3-δ The introduction of 5% Mo into the B cation site induces an increase in crystal symmetry and the reaction rate constant increases from 0.119 min -1 Increased to 0.289min -1 However, increasing the Mo dopant to 10%, maintaining the crystal symmetry did not further improve the paracetamol removal efficiency, showing a similar rate constant of 0.263 min -1 . Considering that the activation properties of the entire MPB region are enhanced. Compared with other cubic perovskite phases, LCMO020 exhibits weaker PMS activation performance, which can be attributed to the presence of the inert La2MoO6 phase, which reduces the proportion of the active perovskite phase. Figure 4 b is the result of spectrophotometric determination of PMS concentration at different activation times. The PMS decomposition rate follows the sequence LCMO005>LCMO010>LCMO020>LCO, which is related to the removal efficiency of paracetamol. The degradation rate of paracetamol is faster than that of PMS, which indicates that the oxidant concentration is too high in the degradation experiment. With LCMO as the catalyst, the TOC removal efficiency is 56.8% after 60 min of reaction, indicating that the mineralization degree of paracetamol is significant, which is further confirmed by LC-MS. The peak value of paracetamol decreases sharply over time, and the appearance and disappearance of various degradation intermediates can be observed.
[0036] MeOH, TBA and FFA were used as OH, SO4 ·- and singlet oxygen scavengers were used for quenching experiments. TBA has a high reactivity with OH, such as Figure 5As shown in a, at 50 mM and 100 mM TBA concentrations, the removal of paracetamol was slightly inhibited, indicating that free ·OH did not contribute much to the degradation process. 1 O2 may also be involved in the degradation process, because some perovskites can also catalyze the activation of PMS such as Figure 5 As shown in a, medium concentration of FFA has a slight inhibitory effect on the degradation of paracetamol, indicating that 1 O2 participated in, but did not dominate, the removal of paracetamol. However, after the addition of 50mM and 100mM MeOH, the removal of paracetamol was significantly inhibited, reaching 60.2% and 51.7% in 60min, respectively. By introducing the LCMO005 catalyst in the solution, a significant change in the PMS concentration was observed, which clearly demonstrated the extremely high performance of this catalyst for PMS activation. In addition, by adding 100mM FFA or MeOH as free radical scavengers, the activation of PMS remained unchanged, i.e., due to the SO4 ·- Trapped by methanol, the concentrations of PMS decrease, but they also oxidize paracetamol. Figure 5 c shows the PMS activation rates on different perovskite catalysts in the presence of methanol as a radical scavenger. As expected, the trends observed correlate with those without scavengers, i.e., the LCMO005 perovskite shows the best pollutant degradation and the undoped LCO compound shows the worst activation. To confirm the chemical probe experiments, we further performed ESR measurements using DMPO and TEMP as spin trapping agents to identify the generated radicals. Figure 5 d (top) shows that PMS alone (control signal) cannot oxidize DMPO at a concentration of 0.5 mM.
[0037] Figure 6 a shows the evolution of the open circuit potential (OCP) for a total of 1200 s in constant current mode. It can be observed that in all experiments, the OCP increases significantly with the addition of PMS, which may be due to the adsorption of PMS on the working electrode leading to the redistribution of electron density and PMS activation. The electrochemical activity of LCMO005 is higher than that of the other catalysts, as expected. However, when paracetamol is subsequently added, the change in OCP is negligible. The OCP changes with the addition of organic pollutants, implying that the mediated electron transfer induces the decomposition of PMS. Therefore, the electron transfer process may not explain the activation of PMS and, concomitantly, the removal of paracetamol. As Figure 6As shown in (b), the current decreased significantly in all tests with the addition of PMS, showing the most obvious signal for LCMO005. This can be explained by the rapid electron transfer from the catalyst to the PMS, leading to the activation of the PMS and the generation of free radicals. In addition, the amount of current reduction may be roughly related to the removal efficiency of paracetamol. The subsequent addition of paracetamol did not lead to a significant current drop, which is consistent with the previous OCP test and excludes PMS activation through mediated electron transfer.
[0038] The electronic structure of transition metals is generally considered to be relevant to the PMS activation performance, so XAS measurements were performed based on the Cok edge and Mo XAS edge evolution to investigate the changes in valence state and coordination environment. Figure 7 A magnification of the absorption edge is shown in a, where the valence state of cobalt in different samples follows the trend of LCO>LCMO005>LCMO010>LCMO020. This trend is consistent with our expectation that Co in undoped LCO compounds 3+ It further decreases with increasing Mo content. We observed that in order to examine this unusual behavior, we carefully analyzed the XPS spectra of all compounds, since oxygen vacancies can be associated with the so-called "oxygen lattice" and "surface oxygen" parameters. A high "oxygen lattice" / low "surface oxygen" component is expected to be associated with a low oxygen vacancy content. Figure 7 As shown in b, the spectra of all samples match the edge position of the molybdenum trioxide standard, indicating that Mo 6+ The pre-edge feature is associated with the 1s-4d excitation of the core electrons to a high-energy empty orbital, and this transition is only allowed in a tetrahedral field. However, it can also be observed in compounds such as MoO3, because Mo is located in a distorted octahedral field, allowing mixing of 4d levels with p orbitals. The intensity of the pre-edge feature observed in all LCO doped samples is reduced compared to MoO3, indicating a higher positional symmetry. It was observed that all samples maintained an octahedral coordination environment. The LCM005 sample has a higher octahedral distortion than LCM010. The enhanced catalytic performance of LCM005 occurs in the region of the composition phase diagram where the crystal structure changes from rhombohedral (LCO) to cubic (LCM010), which is called the morphological phase boundary. As pointed out before, the catalytic reaction in this region may be enhanced. The LCMO020 composite has a higher pre-edge intensity than the other samples due to the tetrahedral coordination of Mo in La2MoO6. The absorption edges of all samples are similar to those of MoO3, indicating that all Mo is in the form of Mo 6+ The Fourier transform (FT) of the k3χ(k) spectrum was performed in the k range of 3-13.5A-1, as shown in Figure 7 c and 7d. For the Cok edge, the peaks at 1.5, 3.1, and 3.5A can be assigned to the Co-O, Co-La, and Co-Co shells. For the Mok edge, the peaks at 1.3 and 3.1A can be assigned to the Mo-O and Mo-La shells. The data were fitted using the strongest single scattering path in the crystal phase, and the fitting results were in good agreement with the previous XRD refinement results. In all samples, Co ions are octahedrally coordinated with O ions, which is consistent with what is expected from the crystallographic data and is consistent with the low intensity of the front edge peak in the XANES spectrum.
[0039] LaCo 1-x Mo x O 3-δ (x = 0, 0.05, 0.1 and 0.2) Perovskite activation of PMS occurs via a free radical process.
[0040] ≡Co 2+ / Mo 5+ +HSO5 - →≡Co 3+ / Mo 6+ +SO4 ·- (SO4 2- )+OH - (·OH)
[0041] ≡Co 3+ / Mo 6+ +HSO5 - →≡Co 2+ / Mo 5+ +SO5 ·- +H +
[0042] SO4 2- + OH→SO4 ·- +OH -
[0043] ≡Mo 5+ ≡Co 3+ →≡Mo 6+ +≡Co 2+
[0044] HSO5 - →SO5 2- +H +
[0045] SO5 2- +HSO5 - →HSO4 - +SO4 2- + 1 O2
[0046] ≡Co 2+ / Mo 6+ +HSO5 - +V o →≡Co 3+ +SO4 ·- +H + +O 2-
[0047] SO5 ·- +O 2- →SO4 - +O2+V o
[0048] refer to Figure 8 As shown, catalyst and PMS dosage, initial pH and coexisting ions have an impact on the removal efficiency. Figure 8 a shows the effect of catalyst dosage. When the catalyst dosage increased from 0.1 to 0.2 g / L, the paracetamol removal efficiency increased from 75.1% to 96.3% within 10 min, which may be due to the increase in PMS activated active sites. Further increasing the catalyst dosage from 0.2 g / L to 0.5 g / L showed a monotonous increase in efficiency, K obs The value increased from 0.28 to 0.41min -1 This may be due to the fact that the dosage of the catalyst provides sufficient reaction sites, while the reaction rate is limited by the PMS concentration rather than the density of reaction sites. Figure 8 b is the degradation results of paracetamol under different PMS doses (0.1mM-1mM). It can be observed that the degradation efficiency of paracetamol increases with the increase of PMS dose. When the PMS dosage reaches 0.5mM, 96% of paracetamol is removed within 10min. From 0.5mM to 1mM, the corresponding dosage increases from 0.28min -1 Increase to 0.5min -1 . When the PMS dosage was equal to or lower than 0.3 mM, the catalyst was clearly unable to completely degrade paracetamol. Since the activation mechanism is based on the generation of ROS, such low PMS concentrations cannot be considered as a sufficient source of oxidative species in the dark. Hazardous contaminants due to the presence of different species in the solution. The initial pH of the 10 mg / L paracetamol solution plus 0.2 g / L catalyst and 0.5 mM PMS was 3.3. Before all degradation experiments were performed using 1 M nitric acid and 1 M sodium hydroxide solutions, the solution pH was adjusted to neutral (7 ± 0.2). Considering the minimal demand for nitric acid during the pH adjustment process, the oxidative properties of nitrate anions can be ignored. Effect of initial pH on paracetamol removal as shown in Figure 3. Figure 8c. When the pH value was between 3 and 9, the removal of paracetamol was highly acceptable, while when the pH value reached 11, an inhibitory effect was observed. This can be explained by the fact that pH affects the presence of the main species in the PMS solution. When the pH is in the range of 3-9, PMS is mainly present in the form of HSO5 2- (pKa1(H2SO5)<0, pKa2(H2SO5)=9.4). When the pH increases to 11, SO5 2- will become the dominant species, with HSO5 2- This will not be conducive to the generation of ROS. Figure 8 d, in 2 mM Cl - ,HCO3 - andNO3 - The removal efficiency of paracetamol was not greatly affected by the presence of - The presence of may also be involved in the direct decomposition of PMS, generating weaker oxidants and free radicals, not SO4 ·- and ·OH. When the concentration increases to 10mM, HCO3 - Has a higher scavenging effect, while NO3 - There was little effect on the removal of paracetamol.
[0049] XRD pattern of cyclic LCMO005 ( Fig. 9 a) shows that there is no obvious structural change after continuous cycling experiments. Fig. 9 As shown in Figure b, with the increase of continuous reaction cycles, the paracetamol removal efficiency decreased slightly, and the paracetamol removal reached 95% within 30 min in the fifth cycle. Fig. 9 c shows that doping LCO with Mo significantly reduces the leaching rate of Co. Using LCMO005 as the catalyst, 0.196 mg / L Mo leaching was observed at pH 7.
[0050] Fig.10a shows the results obtained for the degradation of paracetamol (initial concentration 10 mg / L) in a photoreactor when PMS (0.5 mM), UVA or UVC were applied. During the photocatalytic process, the degradation of the pollutant was negligible, i.e., no PM mass was present in the reaction medium. Paracetamol was rapidly removed in the dark due to the rapid generation of ROS by the catalyst. The performance of the LCMO005 perovskite was slightly higher when deposited in the reactor than when deposited in suspension, indicating that the deposition process did not affect the activation of the PMS. The best degradation was achieved by combining pre-magnetic stimulation with UVC irradiation. During the photocatalytic process, the degradation of the pollutant was negligible, i.e., no PM mass was present in the reaction medium. Paracetamol was rapidly removed in the dark due to the rapid generation of ROS by the catalyst, as demonstrated by previous experiments in the batch laboratory. The performance of the LCMO005 perovskite was slightly higher when deposited in the reactor than when deposited in suspension, indicating that the deposition process did not affect the activation of the PMS. Fig.10 Figure b shows that the PMS / UVC rapid degradation produces high concentrations of intermediates at the initial reaction, followed by a progressive mineralization that is finally reached in 50 min. This fact confirms the existence of a synergistic effect between UVC irradiation and PMS activation, which not only enhances the decomposition of paracetamol but also reduces different generated organic compounds, such as reaction intermediates. Tests with PMS and UVA showed a more complex degradation process that affects paracetamol and intermediates in different ways. First, in the early stages of the PMS / UVA process, the degradation of paracetamol dominated, but once the intermediates were generated, ROS species might be involved in the oxidative competition between the degradation of the target pollutant and the intermediates. Since this competition was not observed in the PMS / UVC degradation spectrum. At 30 min, the degradation of paracetamol could be observed, and at 50 min, the intermediates also reached complete mineralization. On the other hand, although paracetamol was easily degraded in the dark photoreactor, the intermediates could not be completely removed from the solution due to the strong resistance of this byproduct. The removal of the formed reaction intermediates was more effective when the catalyst was used in suspension ( Fig.10 b), but the turbidity is 72.02FTU, which can reduce the effect of ultraviolet radiation.
[0051] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A doped perovskite catalyst for enhancing PMS activation, characterized in that: The catalyst has the chemical formula LaCo 1- x Mo x O 3-δ Represents, where the value of x is between 0 and 0.2, and the catalyst has doped Mo atoms located in the B site of the perovskite structure.
2. The catalyst according to claim 1, characterized in that The catalyst is prepared by a sol-gel method.
3. The catalyst according to claim 1 or 2, characterized in that During the preparation of the catalyst, citric acid is used as a complexing agent.
4. A method for preparing a catalyst as claimed in any one of claims 1 to 3, characterized in that The following steps are involved: S1. Add 10 mmol of La(NO3)3·6H2O, Co(NO3)2·6H2O and (NH4)6Mo7O 24 4H2O was dissolved in 20mL of deionized water and 20mmol of citric acid was added as a complexing agent; S2. The synthesized mixture was heated at 80°C under continuous magnetic stirring until a gel was formed. The obtained gel was further dried in an oven at 110°C for 12 hours until a gel was formed; S3. The dried gel was calcined at 700°C for 5 hours to obtain a catalyst.
5. The method according to claim 4, characterized in that The heating rate of the calcination process was 5°C / min.
6. A method for degrading organic pollutants using the catalyst according to any one of claims 1 to 3, characterized in that The following steps are involved: S1. Adding PMS and a catalyst to a solution containing organic pollutants; S2. Maintain the reaction for a certain period of time in the absence of light or with light to degrade organic pollutants.
7. The method according to claim 6, characterized in that The organic contaminant is selected from acetaminophen (paracetamol).
8. The method according to claim 6 or 7, characterized in that The amount of the catalyst used is 0.1 to 0.5 g / L.
9. The method according to claim 6 or 7, characterized in that The amount of PMS used is 0.1 to 1 mM.
10. The method according to any one of claims 6 to 9, characterized in that The initial pH value of the reaction system is 7±0.
2.
11. The method according to any one of claims 6 to 9, characterized in that The temperature of the reaction system is 25±0.5°C.
12. The method according to any one of claims 6 to 11, characterized in that The light is UVA or UVC.